2023
DOI: 10.3390/w15111992
|View full text |Cite
|
Sign up to set email alerts
|

Internal Erosion Stabilization of Cohesionless Soil Using Lime

Abstract: Soil embankments are valuable for the adequate reserve and supply of water to multiple industries. However, they are susceptible to internal soil erosion, which may ultimately lead to structural collapse. To counteract this issue, soil stabilization is practiced in the construction industry. This paper proposes the internal erosion stabilization of cohesionless soil using quicklime. For this research, two cohesionless soil types were investigated and treated with quicklime: poorly graded and well-graded cohesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Factors include soil water content; unit weight; plasticity index; void ratio; soil swell; and percent passing sieve #200, soil pH, and clay minerals [4]. Other studies [5,6] showed that internal soil erosion is affected by soil type, water and material properties, and soil-piping resistance relationships. Generally, these factors resemble the physical and mineral composition of the soil [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Factors include soil water content; unit weight; plasticity index; void ratio; soil swell; and percent passing sieve #200, soil pH, and clay minerals [4]. Other studies [5,6] showed that internal soil erosion is affected by soil type, water and material properties, and soil-piping resistance relationships. Generally, these factors resemble the physical and mineral composition of the soil [4].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of internal erosion are recognized in hydraulic structures, such as piping, suffusion, blowout (heave, uplift), Suffusion, and backward erosion [5][6][7]. Piping involves the formation of a continuous tunnel, and as a result, water will flow between the upstream and downstream of the earth structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations